2020
DOI: 10.1038/s41598-019-57359-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Determinants of Lung Function until Late Infancy among Infants Born Preterm

Abstract: to investigate the evolution of lung function in preterm infants with and without bronchopulmonary dysplasia (BpD) and to determine the perinatal characteristics associated with indexes of lung function in later infancy. Longitudinal lung function assessments were performed at approximately 6, 12, 18, and 24 months of corrected age in preterm infants. Perinatal characteristics were further analyzed to ascertain the determinants of lung function indexes. Although all preterm infants (n = 121; 61 without BPD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
3
6
1
Order By: Relevance
“…Because the majority of the preterm group in this study had moderate-to-severe BPD (14 out of 23 children), children in this group still demonstrated poorer-than-average baseline lung function. 24 Interestingly, our results showed no differences in Crs between three groups. Since the symptom of wheezing originated from obstruction of small airway, the pulmonary elasticity of these children with recurrent wheezing will be comprehensible.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Because the majority of the preterm group in this study had moderate-to-severe BPD (14 out of 23 children), children in this group still demonstrated poorer-than-average baseline lung function. 24 Interestingly, our results showed no differences in Crs between three groups. Since the symptom of wheezing originated from obstruction of small airway, the pulmonary elasticity of these children with recurrent wheezing will be comprehensible.…”
Section: Discussioncontrasting
confidence: 49%
“…Studies have shown that young children with preterm birth have significant airway obstruction. 24,25 Respiratory dysfunction was shown to be even more pronounced in + MODEL children with BPD. 24 Some researchers have speculated that airway obstruction results from inflammatory insults affecting the conducting bronchioles during the late canalicular or early saccular stage of lung development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These recent findings suggest that ex-preterm children with early reduced lung function compared to term controls could improve lung function over time, especially in absence of BPD ( 15 , 25 , 27 ). According to these findings, we speculate that the lung function was normal in our study population at 11 years of age probably because their lung function improved over time.…”
Section: Discussionmentioning
confidence: 91%
“…Few longitudinal studies were performed. A recent longitudinal study assessing lung function at different time points (6, 12, 18, and 24 months) found that lung function in preterm infants with mild to moderate BPD improved gradually ( 25 ).…”
Section: Discussionmentioning
confidence: 99%